Divination and prediction in early China and ancient Greece - Raphals, Lisa Ann, 1951- (Cambridge : Cambridge University Press, 2013)
"Divination was an important and distinctive aspect of religion in both ancient China and ancient Greece, and this book will provide the first systematic account and analysis of the two side by side. Who practised divination in these cultures and who consulted it? What kind of questions did they ask, and what methods were used to answer those questions? As well as these practical aspects, Lisa Raphals also examines divination as a subject of rhetorical and political narratives, and its role in the development of systematic philosophical and scientific inquiry. She explores too the important similarities, differences and synergies between Greek and Chinese divinatory systems, providing important comparative evidence to reassess Greek oracular divination"--
"This book is an exploration of divination and prediction in Chinese and Greek antiquity, but it is also a part of two ongoing interdisciplinary and intercultural explorations that have informed my scholarly work. One is the engagement between the disciplines of philosophy and history from a perspective also informed by anthropology. The other is the comparative study of Chinese and Greek antiquity from a shifting viewpoint informed by all three disciplines"--
Machine generated contents note: Preface; 1. Introduction; 2. Sources; 3. Theorizing divination; 4. Practitioners; 5. Methods; 6. The questions; 7. Consultors; 8. Mantic narratives; 9. Divination and systematic thought; 10. Conclusions; 11. Glossary; 12. Appendices.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Divination -- China; Divination -- Greece; HISTORY -- Ancient -- General; Divination; China; Greece; BODY, MIND & SPIRIT / Spirituality / Paganism & Neo-Paganism; RELIGION / Antiquities & Archaeology; Electronic books